Effect of bromocriptine and metoclopramide on serum prolactin levels in patients with amyotrophic lateral sclerosis. - Szulc-Kuberska, J (1988)
Secretion of prolactin in nine patients with amyotrophic lateral sclerosis and in seven healthy men was investigated with the use of metoclopramide stimulation and bromocriptine inhibition tests. Blood serum prolactin concentration was determined in the basal state and 30, 60 and 120 minutes after oral administration of 10 mg metoclopramide or 2.5 mg bromocriptine. A period of 3 days intervened between testing each drug in the same individual. It was shown that basal prolactin levels in amyotrophic lateral sclerosis patients and the controls did not differ significantly, whereas in the metoclopramide stimulation test seven amyotrophic lateral sclerosis patients showed a very exaggerated response. The mean value of maximal prolactin increment was 1609.90% (SD 456) in comparison with the control group 638.3% (SD 89.7) (p less than 0.01). In the bromocriptine inhibition test the mean value of maximal prolactin percentage decrement was 50.4% (SD 6.1) in amyotrophic lateral sclerosis and 66.5% (SD 5.3) in the controls and this difference was statistically insignificant. These data suggest that exaggerated prolactin response to metoclopramide in amyotrophic lateral sclerosis may be a result of a decreased activity of central dopaminergic neurons.